To solve for the correct function notation based on the given recursively defined formula, let's first clarify the definitions provided:
- The initial term \(a_1 = -3\).
- The recursive relation is defined by \(a_n = a_{n-1} + 4\).
From the recursive definition, we can express this in function notation:
- We can define a function \(f(n)\) such that:
- \(f(1) = -3\) (the initial value matches \(a_1\))
- The recursive relationship \(f(n) = f(n-1) + 4\) (mirroring \(a_n\) definition).
Now, let's evaluate the options provided:
-
a(1) = -3 ; f(n) = f(n - 1) + 4
- This means \(a_1 = -3\) and \(f(n) = f(n - 1) + 4\). This is not consistent as \(a\) and \(f\) should represent the same sequence.
-
f(1) = -3 ; f(n) = f(n-1) + 4
- This correctly shows \(f(1) = -3\) and that \(f(n)\) follows the same recursive definition.
-
f(1) = -3 ; f(n) = f(a_{n-1}) + 4
- This introduces the incorrect reference \(f(a_{n-1})\), deviating from the original recursive structure.
-
f(1) = -3 ; f(n) = a_{n - 1} + 4
- This incorrectly changes the function's recursive nature, as it suggests direct calculation of \(a_{n-1}\).
-
f(1) = -3 ; f(n) = f(n - 1) + 4
- Similar to option 2, but with a slight formatting difference.
Given the analysis, the correct function notation is:
f(1) = -3 ; f(n) = f(n - 1) + 4.
Thus, response option 2 is the correct option.